Kinetic closed chain isokinetic values in football players: Pilot test - Loeza Magana, P.; Fritzler-Happach, W.; Barrios-González, J. (Archivos de medicina del deporte, 2017)
Objectives: To determine the feasibility of an isokinetic test for lower limbs in kinetic closed-chain in football players in two moment of the season, in addition to obtaining their reference values of peak force and power output. Design: This is a longitudinal, prospective, observational study with a descriptive phase and comparative phase and open. Methods: 16 professional football players from second division of Mexican League between 17 and 21 years were evaluated, making a isokinetic testing for lower limbs in kinetic closed chain at 60 °/s, 10 repetitions, at the beginning and end of the season. Results: The analysis was realized by laterality. Isokinetic reference values were obtained in this group of players for force (Nm) and power (W); the difference of peak force between both sides of the extensors chain was 5.45% initially and 9.52% at the end; for flexors was 14.30% and 9.19% at the end; for the flexor/extensor relationship was 23% initially an 24% in the final test. The progression between the beginning and the end of the season showed increased isokinetics values between measurements of non-dominant mainly muscle groups. Conclusion: The test meets the characteristics required to perform a new test, is applicable and useful for evaluating individual performance in the biomechanics of muscle strength and power at low speed in a functional muscle chain, multiaxial and will identify imbalances, prevent injuries and even make assessments after recovery in the event of an injury.